Translation-Oriented Transdisciplinary Practices: From Organisms to Augmented Data and Translation Sculptures - Demirel, Emine Bogenc; Gorguler, Zeynep (ISTANBUL UNIV, FAC LETTERS, 2021)
While today's digital technologies support social movements towards democratization and civilisation of the individual, they also increase data-based inequalities. With the transition to the network society, we are witnessing translation practices and translator identities reconstructed around digital networks today. However, transdisciplinary concepts and approaches gain importance as a result of the edge effects that translation establishes with the fields of science, art and technology (Demirel and Gorgoler, 2020). With this in mind, translation is considered a new media practice within the scope of the relevant research. In this context, translation-based microscope performances produced in the bioart movement, which are shaped as a new media art type, are discussed within the framework of the mentioned transdisdplinary concepts and approaches. In the first stage, the augmented data and translation sculptures produced by the new media artist Aysegiil Suter based on the microscopic movements of cell tissues are analyzed in the focus of source and target content. In this context, the sculptures Miaospheres, Fight Above Cells and Cryztallization and their biological data constitute the fieldwork of the research. Later, in the conversation with the relevant media artist, or in other words, the translator, regarding the production tactics and performance styles she adopted, the projections of the transdisciplinary concepts and approaches mentioned above are sought. Questioning translation practice and translator identity around the bio-art movement brings together different perceptions of the data reality. As a result, grasping bio-art-oriented production forms as a transdisciplinary translation practice and process also sheds light on the social movements towards democratization shaped around the facts of the data.
Keywords: Translation practice; transdisciplinary approach; bio art; edge relations; democratization; Linguistics